The safety of outpatient total shoulder arthroplasty: a systematic review and meta-analysis - Abdulaziz F. Ahmed (14150082) (2022)
Purpose To meet the increasing demands of total shoulder arthroplasty (TSA) while reducing its financial burden, there has been a shift toward outpatient surgery. This systematic review and meta-analysis aimed to evaluate the safety of outpatient TSA. Methods The primary objective was to compare re-admission rates and postoperative complications in outpatient versus inpatient TSA. The secondary objectives were functional outcomes and costs. PubMed, Google Scholar, and Web of Science were searched until March 28, 2020. The inclusion criteria were studies reporting at least complications or readmission rates within a period of 30 days or more. Results Ten level III retrospective studies were included with 7637 (3.8%) and 192,025 (96.2%) patients underwent outpatient and inpatient TSA, respectively. Outpatient TSA had relatively younger and healthier patients. There were no differences between outpatient and inpatient arthroplasty for 30- and 90-day readmissions. Furthermore, unadjusted comparisons demonstrated significantly less total and major surgical complications, less total, major, and minor medical complications in favour of outpatient TSA. However, subgroup analyses demonstrated that there were no significant differences in all complication if the studies had matched controls and regardless of data source (database or nondatabase studies). The revision rates were similar between both groups at a 12–24 months follow-up. Two studies reported a significant reduction in costs in favour of outpatient TSA. Conclusion This study highlights that outpatient TSA could be a safe and effective alternative to inpatient TSA in appropriately selected patients. It was evident that outpatient TSA does not lead to increased readmissions, complications, or revision rates. A potential additional benefit of outpatient TSA was cost reduction. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-021-04940-7